'An unpublished letter by Sigmund Freud on the Shakespeare authorship question'. Issue 2 (2nd July 2016) - Waugaman, Richard M.
ABSTRACT: This article provides the text of the English translation of Sigmund Freud's previously unpublished 1935 letter to Percy Allen, the only known letter in which Freud expresses his unqualified support for the theory that 'William Shakespeare' was the pen name of Edward de Vere, Earl of Oxford (1550–1604). The article summarizes the literature on Freud's authorship views, showing that scholars who disagree with Freud on this matter have minimized his opinion by pathologizing it, or emphasizing Freud's reservations about the matter. The prevailing theory as to who wrote Shakespeare, on close examination, turns out to be based primarily on circular thinking, confirmation bias, tradition, authority, groupthink, and enforcement of a taboo against the presentation or objective consideration of conflicting evidence. In addition, it originated before we had a better understanding of the high frequency of anonymous, pseudonymous, and allonymous literature in Elizabethan England. The reputations enjoyed by leading Shakespeare scholars lead nonspecialists to assume that these experts can be trusted to tell us who wrote Shakespeare. Unfortunately, Shakespeare scholars falsely claim absolute certainty that they know that 'Shakespeare wrote Shakespeare.' Freud's dissenting opinion has been supported by increasing evidence since 1935.